Agricultural water saving through technologies: a zombie idea. (1st November 2021) - Pérez-Blanco, C Dionisio; Loch, Adam; Ward, Frank; Perry, Chris; Adamson, David
Abstract: A zombie idea is one that has been repeatedly refuted by analysis and evidence, and should have died, but clings to life for reasons that are difficult to understand without further investigation. The perception that investments in modern irrigation systems automatically save water constitutes a zombie idea. On face value, most would accept that modernizing irrigation systems makes sense: agriculture represents 70% of global water withdrawals while physical irrigation efficiencies range between 25% and 50% worldwide—that is, most of the water entering the irrigation system never makes it to the targeted crop. However, the impacts of modern irrigation systems are complex, and as we show, usually have the opposite effect to that intended through altered cropping and water application decisions by farmers, that aggravate water scarcity. This paper investigates how this zombie idea forms; why it persists, even when proven wrong by scientific evidence; and how to overcome it.